Specific Resistance of Barley to Powdery Mildew, Its Use and Beyond. A Concise Critical Review - Dreiseitl, Antonín (Genes, 2020)
Powdery mildew caused by the airborne ascomycete fungus Blumeria graminis f. sp. hordei (Bgh) is one of most common diseases of barley (Hordeum vulgare). This, as with many other plant pathogens, can be efficiently controlled by inexpensive and environmentally-friendly genetic resistance. General requirements for resistance to the pathogens are effectiveness and durability. Resistance of barley to Bgh has been studied intensively, and this review describes recent research and summarizes the specific resistance genes found in barley varieties since the last conspectus. Bgh is extraordinarily adaptable, and some commonly recommended strategies for using genetic resistance, including pyramiding of specific genes, may not be effective because they can only contribute to a limited extent to obtain sufficient resistance durability of widely-grown cultivars. In spring barley, breeding the nonspecific mlo gene is a valuable source of durable resistance. Pyramiding of nonspecific quantitative resistance genes or using introgressions derived from bulbous barley (Hordeum bulbosum) are promising ways for breeding future winter barley cultivars. The utilization of a wide spectrum of nonhost resistances can also be adopted once practical methods have been developed.
Keywords: Hordeum; Ascomycota; durability of resistance; interakce hostitele a patogenu; Phenotype; barley; šlechtění rostlin; odolnost vůči nemocem; Plant Breeding; ječmen (rod); fenotyp; nemoci rostlin; Plant Proteins; Disease Resistance; Host-Pathogen Interactions; rostlinné proteiny; specific resistance; Blumeria graminis f. sp. hordei; powdery mildew; Plant Diseases; Hordeum vulgare